2005
DOI: 10.1007/s10936-005-6204-y
|View full text |Cite
|
Sign up to set email alerts
|

Spoken Idiom Recognition: Meaning Retrieval and Word Expectancy

Abstract: This study investigates recognition of spoken idioms occurring in neutral contexts. Experiment 1 showed that both predictable and non-predictable idiom meanings are available at string offset. Yet, only predictable idiom meanings are active halfway through a string and remain active after the string's literal conclusion. Experiment 2 showed that the initial fragment of a predictable idiom inhibits recognition of a word providing a congruous, but literal, conclusion to the expression. No comparable effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
1
30
1
3
Order By: Relevance
“…In contrast, the CH assumes that idiom activation is not a continuous process, and does not occur until special elements in an idiom (the idiom key) have been recognized. There are findings in the literature supporting the claim that activation does not spread up to idiom concepts starting from string onset (Tabossi et al, 2005;Tabossi & Zardon, 1993, 1995. However, the present evidence does not discriminate between the two alternatives, and it is compatible with both models.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, the CH assumes that idiom activation is not a continuous process, and does not occur until special elements in an idiom (the idiom key) have been recognized. There are findings in the literature supporting the claim that activation does not spread up to idiom concepts starting from string onset (Tabossi et al, 2005;Tabossi & Zardon, 1993, 1995. However, the present evidence does not discriminate between the two alternatives, and it is compatible with both models.…”
Section: Resultsmentioning
confidence: 81%
“…This is not to say that they were highly predictable. In fact, their average predictability would be considered low or very low in most of the studies that explored the notion (Cacciari & Tabossi, 1988;Tabossi, Fanari, & Wolf, 2005;Tabossi & Zardon, 1993, 1995. However, there is a reliable difference between clichés and idioms, and, more importantly, between conventional and control strings.…”
Section: Resultsmentioning
confidence: 99%
“…At that point the idiom is recognized. In fact, when the initial fragment of a string triggers high expectancy about a final idiomatic conclusion, recognition of a word providing an unexpected (literal) ending is slowed down (Tabossi, Fanari & Wolf, 2005). The point at which the idiom is identified depends on the idiom characteristics (e.g., length, familiarity, semantic transparency, ambiguity) and on previous context, and is usually defined as the word after which the expression becomes highly predictable based on cloze probability values.…”
Section: Processing Idioms: Compositionality and Other Factorsmentioning
confidence: 99%
“…Some strings contain only a content word after the verb (e.g., alzare il gomito/raise the elbow, "drink too much alcohol"), others are much longer (e.g., mettere una pulce nell'or ecchio/put a flea in the ear, "raise suspicion"). Several cross-modal studies have shown that the activation of the figurative meaning of an idiomatic string may occur rather late during the processing of an auditory presented string, and may not yet be available at its offset (Cacciari & Tabossi, 1988;Cacciari, Padovani, & Corradini, 2007;Tabossi & Zardon, 1993, 1995Tabossi, Fanari, & Wolf, 2005). However, other data seem to contradict these results (Titone & Coninne 1994a;Tabossi, Fanari, & Wolf, 2005).…”
Section: Lengthmentioning
confidence: 99%
“…Several cross-modal studies have shown that the activation of the figurative meaning of an idiomatic string may occur rather late during the processing of an auditory presented string, and may not yet be available at its offset (Cacciari & Tabossi, 1988;Cacciari, Padovani, & Corradini, 2007;Tabossi & Zardon, 1993, 1995Tabossi, Fanari, & Wolf, 2005). However, other data seem to contradict these results (Titone & Coninne 1994a;Tabossi, Fanari, & Wolf, 2005). In a recent cross-modal study, verbal idioms were divided into short (i.e., containing only one content word after the verb) and long (e.g., containing more than one content word after the verb).…”
Section: Lengthmentioning
confidence: 99%